Impact of Intelligent Transportation Systems (ITS) on Traffic Improvement for Middle City Scale: A Systematic Literature Review (SLR) - Yudha, Ridho Fhaza Damar; Astapati, Damar Gusti; Pamungkas, Febri Kusbianto; Toruan, Erni Sari Lumban; Prasetijo, Joewono (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Intelligent Transportation Systems (ITS) have rapidly evolved as innovative solutions to improve traffic performance while reducing accident rates. This study is a Systematic Literature Review (SLR) aimed at analyzing the impact of ITS technology implementation on traffic improvement, particularly through the application of traffic warning systems and adaptive traffic management. Based on previous studies, traffic warning systems provide real-time information about road conditions and potential hazards, enhancing driver awareness and reducing the risk of accidents. In addition, adaptive traffic management utilizes sensors and optimization algorithms to adjust traffic light cycle times according to vehicle density, resulting in smoother traffic flow and reduced congestion. The findings of this SLR indicate that implementing ITS significantly contributes to lowering accident rates, improving road safety, and enhancing the efficiency of urban transportation networks.